Analysis of Traffic Growth, Operation and Technology in E-Commerce Platforms in Mexico. - Monreal Pitones, Luis Eduardo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: Compare the growth of traffic, technology, and interaction in online stores in Mexico in periods after 2020, as well as the influence of Content Management Systems [CMS] on the organic positioning of online stores created with these platforms.MATERIAL AND METHOD: A mixed approach was used, combining quantitative and qualitative methods. The quantitative part measures metrics such as traffic, speed, and interaction on e-commerce platforms in Mexico. The qualitative part focuses on investigating the technology used on these platforms.RESULTS: The most used CMS in Mexico are Wix, WooCommerce, Shopify, Prestashop, Mercadoshops, and Magento. The average duration on site varies by platform, and the bounce rate also differs between CMS. Variability is seen in the mobile and desktop site optimization scores on each CMS platform.CONCLUSIONS: Organic traffic and interaction on online stores are influenced by the CMS used. The duration of the visit, the number of pages visited, and the bounce rate are important indicators to evaluate the success of each store.
Keywords: E-commerce; Online stores; SEO; CMS; Digital marketing.